7a + 6b = 3
-7a + b = 25
b = 7a + 25
Solve for a
7a + 6(7a + 25) = 3
7a + 42a + 150 = 3
49a + 150 = 3
49a = -147
a = -3
Solve for b
-7(-3) + b = 25
21 + b = 25
b = 4
Check answers
7a + 6b = 3
7(-3) + 6(4) = 3
-21 + 24 = 3
-7a + b = 25
-7(-3) + 4 = 25
-21 + 4 = 25
Answers:
a = -3
b = 4
Solve the elimination method
7a + 6b = 3
-7a +b = 25
The solution of the system is?
2 answers
7 a + 6 b = 3
+
-7 a + b = 25
________________
7 a + ( - 7 a ) + 6 b + b = 3 + 25
7 b = 28 Divide both sides by 7
7 b / 7 = 28 / 7
b = 4
7 a + 6 b = 3
7 a + 6 * 4 = 3
7 a + 24 = 3 Subtract 24 to both sides
7 a + 24 - 24 = 3 - 24
7 a = - 21 Divide both sides by 7
7 a / 7 = - 21 / 7
a = - 3
Proof :
-7 a + b = 25
- 7 * ( - 3 ) + 4 = 25
21 + 4 = 25
+
-7 a + b = 25
________________
7 a + ( - 7 a ) + 6 b + b = 3 + 25
7 b = 28 Divide both sides by 7
7 b / 7 = 28 / 7
b = 4
7 a + 6 b = 3
7 a + 6 * 4 = 3
7 a + 24 = 3 Subtract 24 to both sides
7 a + 24 - 24 = 3 - 24
7 a = - 21 Divide both sides by 7
7 a / 7 = - 21 / 7
a = - 3
Proof :
-7 a + b = 25
- 7 * ( - 3 ) + 4 = 25
21 + 4 = 25